Kearifan Lokal dan Hukum Adat Suku Dani di Papua - Merina, Bresca; Muhaimin, Muhaimin (Universitas Proklamasi 45, 2023)
Papua's cultural wealth will make a lot of positive contributions developing behavior and policy making. In addition, the wealth of Papua not always on natural resources. Papua is also rich in culture. This culture is worthy of being a capital to build the future, even strengthening peace and tolerance in Papua. The purpose of this study is to describe and analyze local wisdom which is a form of existence of customary law that has developed in the Dani Tribe of Papua Province. The research method used is descriptive qualitative with an ethnographic approach. The findings in this study are local wisdom and customary law that developed in Wosilimo Village, Uslimo District, Jayawijaya Regency, Papua, including the Iki Paleg Tradition, Dani traditional clothing, the Dani kinship system and the Wam Mane Ceremony.There are many local wisdoms and customary laws that are spread all over Papua with the myths and culture that develop with them. The Dani tribe, which today still adheres to local wisdom and customary laws, should be appreciated because their ancestral heritage will be well preserved along with the development of the times and human resources that continue to develop in the Dani tribe, local wisdom and customary law are increasingly being criticized but still preserving this culture as part of the ancestral heritage of the Dani tribe.